Effects of the lifestyle intervention program GLICEMIA in people at risk for type 2 diabetes: a cluster-randomized controlled trial - Schmiedel, Karin; Mayr, Andreas; Fießler, Cornelia; Schlager, Helmut; Friedland, Kristina (Diabetes Care, 2015)
The aim of this study was to assess the efficacy of a 12-month prevention program conducted in 42 community pharmacies in reducing the risk for diabetes.In a cluster-randomized controlled trial in 1,092 participants, mean change in the risk for diabetes (indicated by the Finnish Diabetes Risk Score [FINDRISC]) between intervention and control groups was calculated. In the intervention program GLICEMIA, three appointments with individual counseling and five educational group sessions were combined, whereas in the control group, only information about the participants' health was obtained in three assessments.After adjusting for cluster structure and differences in baseline characteristics, improvement in FINDRISC in the intervention group was 0.74 points (95% CI 0.42-1.04) above the control group.The GLICEMIA program shows the feasibility of a pharmacy-based intervention and leads to a significant modest reduction in diabetes risk score but does not reduce the rate of diabetes progression over 1 year.
EVALuna2:5529